Excursio per Orientem: eastern subjects in Tacitus' Histories and Annals. - Miravalles, Ana Cecilia (Durham University, 2017)
This study examines Tacitus' treatment of eastern topics in sections of the Histories and the Annals related to trips from or to Rome. It aims to show that those sections, though involving non-Roman subject matter, are essentially connected with the main subject matter about Roman politics that articulate the narratives of the Histories and the Annals: the consolidation of the Principate, the legitimacy of the emperors' power, the territorial expansion of the empire and the responses of the Roman institutions to those new realities. Thus the internal structure and the connection with the surrounding narrative of each episode as well as the references to mythical and historical accounts and characters (from remote and recent history), and to ruins, sanctuaries and cult statues are explored. Chapter 1 (Titus' trip and the consultation of the sanctuary of Paphos, Hist. 2. 1-4) suggests that the remoteness of the place and of the traditions and Titus' oracle, do not divert the attention, but emphasise the beginning of the Flavian revolt. Chapter 2 examines Vespasian's visits to the sanctuaries in Mount Carmel in Syria and in Alexandria in Egypt (Hist. 2. 78 and 4. 81-84). Chapter 3 deals with the account ofthe siege of Jerusalem and the digression on the Jews (Hist. 5.1-13). Chapter 4 is about Germanicus' eastern trip (Ann. 2. 56-61). And finally, chapter 5 (Ann. 2.47; 3. 60-65; 4. 13-14; 4. 55-56 and 12. 61-63) examines the interventions in the Senate of eastern ambassadors who ask for concessions such as tax remissions, rights of asylum and rights for constructing temples. The argument is made that these sections introduce a further temporal and geographical perspective for the understanding of the main axis of the Histories and of the Annals.